The question of the syntactic status of substantives in Russian identity sentences - Natalia V. Knyazeva (Publishing house "Sreda", 2024)
A multi aspect study of bisubstantive sentences of characterizing semantics is necessary to solve complex problems of syntactic analysis. The grammatical specificity of bisubstantial sentences lies in the morphological identity of the predicative minimum. The study has theoretical and practical tasks: identify the structural, semantic and communicative organization of sentences, propose methodological recommendations for syntactic analysis of sentences. The material of the study is modern literature. Analytical and descriptive methods are used to analyze the linguistic material. The problems of teaching syntactic analysis of sentences are identified through experimental methods. The main conclusions of the study: syntactic analysis of bisubstantial sentences should consist of traditional structural and semantic parameters, roles and functions in the semantic structure and communicative organization of a sentence, take into account context, stylistic and pragmatic factors. Syntactic phenomena should be studied from the functional position at all stages and levels of teaching syntax of the modern Russian language.